Evaluating Government Employment and Compensation. (Technical Notes and Manuals; Technical Notes and Manuals ;, 2010)
This technical note provides criteria for evaluating government employment and compensation and options for reform. The note discusses various quantitative indicators that can be used for country analysis and provides an assessment of differences across regions and country groups. It addresses short- and medium-term options for reform and country experiences. Data tables, which can be useful for comparative analysis, are provided. The note underscores that technical analysis of employment and compensation issues must be accompanied by judgment to weigh the tradeoffs between competing objectives.